Atomic/Molecular Layer Deposition for Designer's Functional Metal–Organic Materials. Issue 15 (20th April 2022) - Multia, Jenna; Karppinen, Maarit
Abstract: Atomic layer deposition (ALD) for high‐quality conformal inorganic thin films is one of the cornerstones of modern microelectronics, while molecular layer deposition (MLD) is its less‐exploited counterpart for purely organic thin films. Currently, the hybrid of these two techniques, i.e., ALD/MLD, is strongly emerging as a state‐of‐the‐art gas‐phase route for designer's metal–organic thin films, e.g., for the next‐generation energy technologies. The ALD/MLD literature comprises nearly 300 original journal papers covering most of the alkali and alkaline earth metals, 3d transition metals, and lanthanides as the metal component and a variety of aliphatic, aromatic, and natural organic components. Some of these ALD/MLD processes yield in situ crystalline coordination‐polymer‐ or metal–organic‐framework‐like structures. Another attractive aspect is that many of the metal–organics realized through ALD/MLD are fundamentally new materials, and even unaccessible through conventional synthesis. Here, the current state of research in the field is presented, by i) providing a comprehensive account of the ALD/MLD processes so far developed, ii) addressing the constraints/possibilities for growing in situ crystalline metal–organic films, iii) highlighting some intriguing ALD/MLD materials and their application potential, and iv) making a brief outlook to the future perspectives and challenges in the field. Abstract : Atomic/molecular layer deposition allows the fusion of inorganic and organic components into designer's hybrid materials in a scientifically elegant yet industry feasible way. It can yield unforeseen crystalline metal–organic thin films and elaborated inorganic‐organic heterostructures towards next‐generation advanced applications. This comprehensive review summarizes the research conducted in the field during its decade‐plus history.